Visual Analysis and Right Wing (Populist) Groups - Adami, Angela (PARTECIPAZIONE E CONFLITTO, 2020)
The following article main contribution falls within the domain of methodology as it draws attention on the strength of visual analysis within the field of study of populism. The work elaborates on a visual analy-sis of the posters published to advertise two events – a concert in memory of Jan Palash and the World Congress of Families – organized in Verona in the early months of 2019 by a set of organizations linked to the right and the extreme right and to conservative catholic stances. These politicized organizations carry out a specific type of cultural-political work and operate at the edge of the political sphere, by building alliances with (extreme) right-wing political actors and by lobbying political institutions. The visual analysis is geared at bringing agencies and ambivalences to the fore and allows to uncover (a) the ’communicative camouflage’ of these organizations who spread radical right and catholic conservative messages, traditionally marked by highly recognizable communication features and symbols, in more neutral, moderate and positive forms; (b) the deployment of some populist elements in their communication strategy, such as the reference to welfare chauvinism, to the first Conte government as well as the identification of the ’natural family’ as an homogenizing category associated with the good and moral side of society. While these features are per se not sufficient to define these organizations as fully populist actors, they are nonetheless important to underscore the role played by these organizations in spreading extremely polarized messages in a more digestible way for broader audiences by means of a communicative camouflage and of populist elements in their communication strategy.